2014
DOI: 10.1097/igc.0000000000000124
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Early Predictive Power of Quantitative Magnetic Resonance Imaging Parameters During Neoadjuvant Chemotherapy for Uterine Cervical Cancer

Abstract: Early TVRR, Ve, and the change of Ve could be useful predictors for the treatment effectiveness of NACT. These parameters could help to modify strategy in the early stage of NACT and to choose individualized treatment to avoid the delay of radical treatment, even when NACT is ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…[ 19 ] To the best of our knowledge, few reports have evaluated the predictive power of DWI for determining the NACT outcome for cervical cancer. [ 8 9 ] Based on its molecular diffusion and perfusion properties, IVIM represents a noninvasive method for predicting treatment responses before treatment and for monitoring responses during treatment. We collected a dataset that included 42 cases of cervical cancer and evaluated the predictive value of IVIM parameters in terms of the response to NACT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 19 ] To the best of our knowledge, few reports have evaluated the predictive power of DWI for determining the NACT outcome for cervical cancer. [ 8 9 ] Based on its molecular diffusion and perfusion properties, IVIM represents a noninvasive method for predicting treatment responses before treatment and for monitoring responses during treatment. We collected a dataset that included 42 cases of cervical cancer and evaluated the predictive value of IVIM parameters in terms of the response to NACT.…”
Section: Discussionmentioning
confidence: 99%
“…Diffusion-weighted magnetic resonance imaging (DWI) is a proven quantitative biomarker for the therapeutic response to chemoradiotherapy (CRT) and NACT in cervical cancer. [ 8 9 10 ] Studies have demonstrated significantly different apparent diffusion coefficient (ADC) values between responders and nonresponders after therapy; therefore, DWI may be a good tool for evaluating treatment responses. However, ADCs obtained from DWI with a monoexponential model can be influenced not only by molecular diffusion but by microcirculation or blood perfusion; therefore, ADC values that include perfusion effects may limit the reliability of this tool.…”
Section: Introductionmentioning
confidence: 99%
“…Some proposed genomic, proteomic predictive signature are limited by small sample size and high cost of examination (13,14). Several pioneer studies demonstrated quantitative parameters derived from pre-and post-treatment functional imaging of LACC patients were powerful markers to noninvasively predict early therapeutic response to NACT (15,16). These quantitative parameters allow for characterizing tumor biological process during NACT.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of cost-effectiveness and clinical practicality, MRI-based biomarkers are generally superior to some proposed clinicopathologic, genomic, or proteomic predictors of the NACT response. In addition, comparing quantitative parameters extracted from pre- and post-treatment functional MRI has been demonstrated to improve response assessment by detecting invisible biological properties of cervical tumour [[15], [16], [17]]. However, most research methods are conducted on a post-treatment basis and yield variable diagnostic performances, thereby restricting the utility in the initial decision making regarding NACT.…”
Section: Introductionmentioning
confidence: 99%